Conducta evitativa y su repercusión en la relación con pares en un adulto en tiempos de pandemia - Gurumendi Rodriguez, Jose Alexander (2020)
The development of this project is based on a 25-year-old university adult, who throughout his life has exhibited a type of avoidance behavior, and now in times of pandemic, this situation has become much more complex, since it normally does , he was socially distant now it is more, also the situation he is going through is difficult due to the fact that although he was able to socialize with his peers and have a closeness with them, now it is impossible for him to be close to them and maintain a relationship This has triggered an emotional imbalance, since he limits himself to relating to other people, and his isolation increases every day. For the development of this project, a non-experimental research was carried out, as well as techniques and instruments that in the future will help to determine a diagnosis, so that the necessary measures can be taken to help people who acquire this equitable behavior.